Selected toxic and essential heavy metals in impacted teeth and the surrounding mandibular bones of people exposed to heavy metals in the environment - Malara, Piotr (J Occup Med Toxicol, 2016)
BACKGROUND: The elemental composition of bones and teeth can allow exposure to heavy metals in the environment to be estimated. The aim of this study was to determine whether impacted mandibular teeth and the surrounding bones can be used as biomonitoring media to assess exposure to heavy metals. METHODS: The research materials were 67 impacted lower third molars and samples of the cortical bone removed when the wisdom teeth were surgically extracted. The samples were from people living in two areas with different environmental concentrations of heavy metals. The cadmium, chromium, copper, iron, lead, manganese, and zinc concentrations in the samples were determined by atomic absorption spectrometry with flame atomization. RESULTS: The cadmium and lead concentrations in the impacted third molars and the bones surrounding the teeth were significantly higher for people living in the relatively polluted Ruda Slaska region than for people living in Bielsko-Biala region. Significantly higher chromium, copper, manganese, and zinc concentrations were found in the bones surrounding the impacted teeth from people living in Ruda Slaska than in the bones surrounding the impacted teeth from people living in Bielsko-Biala. The cadmium concentrations in impacted teeth and the surrounding bones were significantly positively correlated. CONCLUSION: The results indicated that impacted mandibular teeth and the surrounding mandibular bones may reflect the exposure of people to cadmium and lead in the environment. This conclusion, however, must be verified in future research projects designed to exclude the possibility of additional dietary, occupational, and other types of exposure to heavy metals.